2020
DOI: 10.1080/14479338.2020.1763177
|View full text |Cite
|
Sign up to set email alerts
|

Talk, talk, talk: exploring idea conversations and the micro-level foundations of knowledge sharing for innovation

Abstract: In this study we explore the drivers and consequences of microlevel instances of knowledge sharing for innovation. We do so by focusing on the temporally bounded conversations that colleagues have about new ideas and we study specifically how the strength of ties between these colleagues influences the duration and breadth of knowledge sharing in the idea-related conversations they have over time. A 14-month on-site field study in a multinational company, in which we mapped 496 dyadic relationships regarding 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 102 publications
(130 reference statements)
0
9
0
Order By: Relevance
“…The testimonies showed how to open creativity is related to the application of complementary expertise (Deichmann et al , 2021) of external actors who use their relationships to generate and improve ideas (Muzzio et al , 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The testimonies showed how to open creativity is related to the application of complementary expertise (Deichmann et al , 2021) of external actors who use their relationships to generate and improve ideas (Muzzio et al , 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The generation and sharing of ideas have been an important action in the interaction of groups and tend to produce positive results in problem-solving (Deichmann et al , 2021), given that individuals who share ideas are exposed to a greater number of new ideas than individuals who generate ideas alone, i.e. collective idea generation has the potential to increase creativity (Paulus and Yang, 2000) when it enables greater group encouragement regarding the individual and greater collective engagement to generate and improve ideas (Harvey and Kou, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…By doing so, we provide empirical evidence for the joint effect of two previously separately studied antecedents of online knowledge sharing. Our study also adds to the emerging stream of literature on the micro-foundations of knowledge sharing (Deichmann et al, 2020). Micro-foundations include actions and interactions at the individual level, which have been argued to be undertheorised yet constitutive for organisational processes (Foss et al, 2010;Gond & Moser, 2019).…”
Section: Theoretical Implicationsmentioning
confidence: 87%
“…Knowledge sharing is of essential value for many organisations in the knowledge-based economy (Deichmann et al, 2020;O'Mahony & Lakhani, 2011). It increasingly takes place in an online environment (Bhagat et al, 2002;Kotlarsky & Oshri, 2005;Lin & Joe, 2012;Taylor, 2004), for example, in online communities (Faraj et al, , 2016O'Mahony & Ferraro, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The researchers selected knowledge-sharing behavior as a mediator because (Radaelli, Lettieri, Mura, & Spiller, 2014) explained that knowledge shared and exchanged between individuals can stimulate their thinking processes, which in turn will generate more new and creative ideas, so that individuals who share knowledge more frequently tend to engage in innovative work behavior, especially in generating, promoting, and implementing innovation. Recent findings from (Deichmann, Moser, & van den Ende, 2021) also imply that if people share knowledge with each other and talk about an idea for a longer period of time and in depth, the outcome of the conversation will benefit the idea being discussed and, as a result, increase the opportunities for innovation. Research has found that knowledge-sharing behavior has a positive impact on innovative workplace behavior (Munir & Beh, 2019) (Nguyen, Nguyen, & Do, 2019).…”
Section: Introductionmentioning
confidence: 99%